2014
DOI: 10.15381/rivep.v25i3.10116
|View full text |Cite
|
Sign up to set email alerts
|

EFECTO DE LA SUPLEMENTACIÓN DE ÁCIDOS ORGÁNICOS SOBRE PARÁMETROS PRODUCTIVOS DEL CUY (Cavia porcellus)

Abstract: RESUMENEl objetivo del estudio fue evaluar el efecto de la suplementación de ácidos orgáni-cos (AO) sobre los parámetros productivos del cuy (Cavia porcellus). Ochenta cuyes machos fueron distribuidos aleatoriamente en 20 unidades experimentales, las cuales se distribuyeron aleatoriamente en cinco tratamientos: T1: Control (dieta base), T2: Antibió-tico Promotor del Crecimiento (APC) (dieta base más 200 ppm de Zinc-Bacitracina), T3, T4 y T5: Ácidos orgánicos (AO) (dieta base más 100, 200 o 300 ppm, respectivam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Regarding the control group (118.6g), treatment 3 in doses of 5 days obtained the highest value (147.7g) compared tos other experimental groups (Table 2). This shows a significant difference (p <0.05) between treatments, which suggests that if there is a positive effect of these organic acids on the weight with which the kits are born (Sánchez-Silva et al, 2014;Upadhaya et al, 2014). Saying this, it is possible that the supplementation with these organic acids added to the diet of the pregnant female has had a direct influence (p <0.05) on the development of the fetus, finally favoring the weight of the kitten (Guevara et al, 2015;Dittoe et al, 2018).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Regarding the control group (118.6g), treatment 3 in doses of 5 days obtained the highest value (147.7g) compared tos other experimental groups (Table 2). This shows a significant difference (p <0.05) between treatments, which suggests that if there is a positive effect of these organic acids on the weight with which the kits are born (Sánchez-Silva et al, 2014;Upadhaya et al, 2014). Saying this, it is possible that the supplementation with these organic acids added to the diet of the pregnant female has had a direct influence (p <0.05) on the development of the fetus, finally favoring the weight of the kitten (Guevara et al, 2015;Dittoe et al, 2018).…”
Section: Resultsmentioning
confidence: 90%
“…The present study did not find a treatment that shows outstanding results for all the parameters evaluated, making use of organic acids (citric acid, propionates and phosphates) potentially due to the normal conditions of a guinea-pig production system. At the literature level, studies with organic acids in guinea pigs are reported, mainly evaluating productive parameters in breeding guinea pigs (Bazay et al, 2014;Sánchez-Silva et al, 2014;Cano et al, 2016), who evaluate only weight gain, dry matter intake and food conversion index, possibly due to the reported positive influence on intestinal cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations